PENGARUH POTONGAN HARGA, KENYAMANAN, INTERAKTIVITAS, DAN KETERLIBATAN TERHADAP NIAT PEMBELIAN IMPULSIF PADA FITUR LIVE STREAMING DI PLATFORM E-COMMERCE - Gunawan, Muhammad Arief; Sukresna, I Made (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT This study aims to analyze the effect of price discount, convenience, interactivity, and involvement on impulsive buying intention with perceived enjoyment as an intervening variable on live streaming at e-commerce platform. Previous research on e-commerce live streaming focused on impulse purchases consisting of several factors, but there were still few and differing significance in using the price discount variable on impulsive buying. Therefore, this research gathered 159 respondents from people who watch and buy product during live streaming e-commerce. The sampling method used is purposive sampling by distributing questionnaires to the respondents. In this research, a theoretical model was developed by proposing five hypotheses that will be tested using a Structural Equation Modeling (SEM) analyzer operated through the SMART PLS 3.0 program. With the result of the research showed that price discount, convenience, interactivity, involvement have significant impact on impulsive buying intention with perceived enjoyment as an intervening variable on live streaming at e- commerce platform